2013
DOI: 10.1177/082585971302900308
|View full text |Cite
|
Sign up to set email alerts
|

The voices of Young New Zealanders Involved in Pediatric Palliative Care

Abstract: The perspectives of young New Zealanders receiving pediatric palliative care (PPC) are not well understood. A qualitative study of the perceptions of 16 PPC patients and their siblings, aged 9 to 18, was conducted through audio and written diary accounts. Inductive thematic analysis revealed several concerns of participants, including special treatment that patients had received, spending time with their families, their feelings of being judged or discriminated against, their sense of being understood themselv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…The relationship between pediatric patients and their families was mentioned in six qualitative studies (Borghi et al, 2014; Flavelle, 2011; Gaab et al, 2013; Hinds et al, 2005; Kortesluoma et al, 2008; Kortesluoma & Nikkonen, 2006). The relationship with the family is interlinked with the relationship with healthcare professionals and peers (Kortesluoma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between pediatric patients and their families was mentioned in six qualitative studies (Borghi et al, 2014; Flavelle, 2011; Gaab et al, 2013; Hinds et al, 2005; Kortesluoma et al, 2008; Kortesluoma & Nikkonen, 2006). The relationship with the family is interlinked with the relationship with healthcare professionals and peers (Kortesluoma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship with the family is interlinked with the relationship with healthcare professionals and peers (Kortesluoma et al, 2008). Children describe their family as the primary source of support (Borghi et al, 2014; Gaab et al, 2013; Hinds et al, 2005). Studies (Flavelle, 2011; Gaab et al, 2013; Kortesluoma & Nikkonen, 2006) have found that the diagnosis affects the relationships among family members.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barriers to obtaining consent included overcoming participants’ attitudes or preconceptions towards research (‘Some parents felt that their son/daughter would be unable to participate as they were either non-verbal or had severe learning disabilities’ 30 ), logistical factors and CYP characteristics (‘Symptoms such as fatigue can keep children in critical condition from participating in research’ 31 )…”
Section: Resultsmentioning
confidence: 99%